The Application of Talaqqi Method to Improve the Pronunciation of Hijaiyah Letters in Children in Pengajian - Zahro Zahro; Imam Tabroni; Cai Jixiong; Lie Jie (Journal of Computer Science Advancements, 2023)
Learning the Qur'an, especially the ability to read the Qur'an, should be taught to children from an early age. In teaching reading the Qur'an teachers can use various methods. One of the methods of reading the Qur'an is the iqro' method. The purpose of the iqro' method is to prepare students to become a qur'ani generation, namely a generation that loves the Qur'an, is committed to the Qur'an and makes it a daily reading and outlook on life. Talaqqi method is a method used by the teacher in listening to the recitation of the Qur'an to his students directly, anywhere with the condition of meeting face to face without the intermediary of other tools. This study aims to describe the teacher's efforts to improve the pronunciation of hijaiyah letters in children at Pengajian Al-Muttaqien Purwakarta, totaling 25 children. Based on the results of research from cycle and cycle II, it can be concluded that the talaqqi method can improve the ability to pronounce hijaiyah letters in children at Pengajian Al-Muttaqien Purwakarta, it can be seen from the results of data analysis, in the first cycle of the first meeting, the percentage of talaqqi can be seen from the results of data analysis.